Black Buddhists and the Black Radical Tradition : The Practice of Stillness in the Movement for Liberation - Vesely-Flad, Rima (Book collections on Project MUSE., 2022)
"This book illuminates distinct Buddhist practices amongst meditators of African descent. It includes interviews, dharma talks, and writings of more than sixty-five Black Buddhist teachers and long-term practitioners. In lifting up the distinctive voices and practices of Black Buddhists within American Buddhism, this book emphasizes the interpretations and practices of Black Buddhists. This book identifies specific causes and conditions for suffering, such as the transatlantic slave trade, the auction block, lynchings, migrations, and contemporary state violence, that have led Black Buddhist teachers to prioritize healing intergenerational trauma as a foundation for Black liberation. In pointing the horrific conditions manifested by patriarchy, misogyny, cisgender normativity, Black Buddhists assert that healing intergenerational trauma is foundational of psychological and spiritual liberation. Relatedly, this book delves into the importance that Black Buddhists place on honoring ancestors-biological and spiritual-as forebears who survived hostile and degrading conditions. Furthermore, this book illuminates the ways in which Black Buddhists privilege the body, even as it has been degraded, as a vehicle for liberation. Finally, this book argues that all of these distinct components of Black Buddhist practice fulfill the quest for psychological liberation evoked in the Black Radical Tradition"--